Case presentation: Breast abscess - Obiozor AC; Obiozor AA (Ibom Medical Journal)
Background: Breast abscess is a localized collection of pus within the breast tissue, often caused by bacterial infection like staphylococcus and salmonella organisms. It typically arises as a complication of mastitis. Breast abscesses, although more prevalent in lactating women, can occur in non-lactating women like in this case presentation and can pose a diagnostic challenge. Predisposing factors includes trauma to the breast, breast surgery, or preexisting conditions like diabetes or immunosuppression. Clinically, a breast abscess presents with symptoms such as localized pain, swelling, redness, and sometimes fever and malaise. Diagnosis, is primarily based on clinical examination, laboratory tests and imaging studies, such as mammography, ultrasound in order to confirm the presence and extent of the abscess. Treatment involves antibiotics to address the infection and drainage of the abscess, either through needle aspiration or surgical intervention, to remove the pus and alleviate symptoms. Prompt treatment is crucial to prevent complications such as sepsis or chronic infection. The prognosis is generally good with timely and appropriate management, although recurrence can occur.